Ni–H-Catalyzed Chemo- and Regioselective Hydroarylation of Vinylsilanes - Brösamlen, Daniel; Oestreich, Martin (Synthesis, 2024)
A chemo- and regioselective hydroarylation of vinylsilanes with (hetero)aryl iodides under Ni–H catalysis is reported. This mild and straightforward protocol furnishes the anti-Markovnikov products in good yields as single regioisomers. This study demonstrates excellent control over the chemoselectivity and complements existing methods for the construction of homobenzylic silanes.
Keywords: cross-coupling; hydroarylation; nickel; regioselectivity; silicon